Occurrence and Risk Assessment of per- and Polyfluoroalkyl Substances in Water Source Protection Area of Southeastern China - He, Shu; Ren, Nanqi (Frontiers in Environmental Science, 2022)
In order to clarify the pollution characteristics and human health risks of PFASs pollutants in typical drinking water sources in Zhejiang Province, this study relies on ultra -performance liquid chromatography-mass spectrometry (UPLC-MS/MS) technology to analyze the pollution of 26 PFASs in 7 reservoirs in Zhejiang Province. The detected concentrations of PFASs were evaluated to further assess the human health risks. Total PFASs concentrations in the seven reservoirs ranged from 1.30 ng L-1 to 24.90 ng L-1. Among the 26 PFASs pollutants analyzed, PFOA and PFBA were the main PFASs pollutants, the detected concentrations of PFOA and PFBS ranging from 0.50 ng L-1 to 13.70 ng L-1 and 0 ng L-1 to 1.70 ng L-1, respectively. Then we evaluated 15 PFASs and calculated the results of the HQ value of the reproductive toxicity and hepatotoxicity of the total PFASs in this study ranged from 2.30 × 10-8 to 1.16 × 10-4 and 9 × 10-8 to 5.24 × 10-4 respectively, which were both lower than 0.01, indicating that there is no significant risk to the human body.